Pengaruh Pengarahan dan Pengawasan Terhadap Efektivitas Kerja Pada Dinas Kelautan dan Perikanan Provinsi Banten - Rahmat Gunawan (Fakultas Ekonomi dan Bisnis Universitas Prima Graha, 2020)
This research have a purpose to know the intervals of guidance and observation can influence the effectiveness work the officer at On duty Oceanic and Fishery of Province Banten. While population in this research is entire/all officer in environment on duty Oceanic and Fishery of Province Banten amounting to 95 people, so that as a whole sum up the officer at On duty Oceanic and Fishery of Province Banten own full scale of population as a whole as much 95 people. Result of analysis by using SPSS version 11 for Windows to show that free variable influence (guidance and observation) to variable trussed (work effectiveness), either through partial and also simultan (together), having influence which are positive and mean the. Visible the mentioned from value significant from each every research variable, what menunjukan that smaller than 5% or (0,000<0,05). Coefficient Determination progressively goodness of ability of variable of guidance and observation explain or explain the variable work effectiveness. While result from value of coefficient Determinasi (R2) of to show of equal to 0,529 or 52,9%. Its meaning, that variable effectiveness work the officer of at On duty Oceanic and Fishery of Province Banten influenced by variable of guidance and observation of equal to 52,9%. While the rest that is equal to 47,1% influenced by other; dissimilar variable outside variable of guidance and observation, what is in research is not analysed furthermore.